Re: fullsimplify problem

*To*: mathgroup at smc.vnet.net*Subject*: [mg52953] Re: fullsimplify problem*From*: Bill Rowe <readnewsciv at earthlink.net>*Date*: Fri, 17 Dec 2004 05:20:28 -0500 (EST)*Sender*: owner-wri-mathgroup at wolfram.com

On 12/16/04 at 3:41 AM, symbio at has.com (symbio) wrote: >Given ( - a / b^2) = = ( + a / b^2), it can be written as (-2 a / >b^2), Huh??? What is it you think can be written as (-2 a / b^2)? subtracting (+a/b^2) from both sides gives (-2 a/b^2) == 0 which clearly reduces to a/b == 0 >but when I use FullSimplify on that equation, I get the >incorrect result ( a / b ) = = 0. Why do you think this is incorrect? What are you expecting? -- To reply via email subtract one hundred and four